Tuberculous tonsillitis - Celik, O.; Yalcin, S.; Hancer, A.; Celik, P.; Ozercan, R. (My University, 1995)
The epidemiology of tuberculosis has changed recently with an increasing incidence of unusual presentations. A case of tuberculous tonsillitis, which is a rare condition, is presented in this report. The manifestations of this entity are tonsillar hypertrophy and painful ulceration. Final diagnosis of tuberculous tonsillitis is usually made after histopathologic examination of tonsillectomy material. Cultures should be obtained from the tissue specimens, and acid-fast bacilli must be investigated to confirm the diagnosis. Systemic signs of tuberculosis may not be seen in this clinical form. These features may confuse tuberculous tonsillitis with malignancies. In this article, general information and literature about tuberculous tonsillitis are reviewed, and a case of tuberculous tonsillitis is reported to draw attention to this rare clinical form of tuberculosis.
Keywords: Aged; Case Report; Diagnosis, Differential; Human; Hypertrophy; Male; Tonsillar Neoplasms; Tonsillectomy; Tonsillitis; Tuberculoma; Tuberculosis; Tuberculosis, Lymph Node; Ulcer; ethambutol; isoniazid; morinamide; rifampicin; aged; article; case report; histopathology; human; human tissue; male; priority journal; tonsillitis; tuberculosis